Silicon photonics for telecom and data-com applications - Asakawa Kiyosh (Institue of Optics and Electronics, Chinese Academy of Sciences, 2020)
In recent decades, silicon photonics has attracted much attention in telecom and data-com areas. Constituted of high refractive-index contrast waveguides on silicon-on-insulator (SOI), a variety of integrated photonic passive and active devices have been implemented supported by excellent optical properties of silicon in the mid-infrared spectrum. The main advantage of the silicon photonics is the ability to use complementary metal oxide semiconductor (CMOS) process-compatible fabrication technologies, resulting in high-volume production at low cost. On the other hand, explosively growing traffic in the telecom, data center and high-performance computer demands the data flow to have high speed, wide bandwidth, low cost, and high energy-efficiency, as well as the photonics and electronics to be integrated for ultra-fast data transfer in networks. In practical applications, silicon photonics started with optical interconnect transceivers in the data-com first, and has been now extended to innovative applications such as multi-port optical switches in the telecom network node and integrated optical phased arrays (OPAs) in light detection and ranging (LiDAR). This paper overviews the progresses of silicon photonics from four points reflecting the recent advances mentioned above. CMOS-based silicon photonic platform technologies, applications to optical transceiver in the data-com network, applications to multi-port optical switches in the telecom network and applications to OPA in LiDAR system.